Controlled Release of the Pineal Hormone Melatonin from Hydroxypropylmethylcellulose/Sodium Alginate Matrices in Aqueous Media Containing Dioctyl Sulfosuccinate - Marilena Vlachou; Athanasia Tsiakoulia; Aphrodite Eikosipentaki (Current Drug Discovery Technologies, 2007)
An investigation of the controlled release profile of mono-layered formulations of the hormone melatonin in modified aqueous media is described. The tablets used were comprised of hydroxypropylmethylcellulose (HPMC K15M) and sodium alginate with melatonin (fully soluble in the dioctyl sulfosuccinate (DSS) containing simulated intestinal solution). Three different sets of tablets (diameters 7.5, 10.0 and 13.0 mm) were tested with respect to the influence of their sizes on the hormone's release; the general trend observed was that tablets with larger surface area values had lower % release. A decrease in the value of Wo, obtained from the ratio [H2O]/[DSS], results to the predominance of DSS conformers in the aqueous media, which are less likely to solubilize melatonin effectively.
Keywords: Melatonin